Chatbot AWARE: A Thematic Literature Review on Chatbot Awareness, Workload-Based Adoption, Responsibility, and Ethics in Higher Education Institutions - Anthony U. Concepcion (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
AI chatbots may improve learning, simplify teaching, and engage students at colleges and institutions. AWARE examined chatbots' effects on instructors and students.  Awareness, ethics, responsibility, and workload-based adoption comprise the framework.  By reviewing 19 scholarly sources, the researchers created the AWARE framework.  Topics were sorted into four groups.  Researchers ought to know the framework's pros and cons and smart uses.  Online chatbots can teach, administer, and collect feedback, according to the study. There are however some problems, like lower emotional intelligence, the risk of disseminating false information, concerns about academic honesty, and the fact that not everyone can access the material. The study shows that chatbots can help with teaching instead of replacing it, as long as there are clear rules and a consistent way of teaching. The lack of lasting empirical evidence concerning the effectiveness of chatbots highlights the imperative for subsequent research aimed at measurable learning outcomes, equitable access, and the establishment of stringent ethical standards for AI integration in higher education.